Output Growth Volatility, Remittances and Institutions (2015)
Purpose – The purpose of this paper is to empirically examine the role of institutions on the remittances– output growth volatility relationship. Design/methodology/approach – The data set of this paper is limited to 71 remittances recipient countries. In an attempt to deal with endogeneity issues, the paper adopts the use of system generalized method of moment (GMM). Findings – First, in consonance with earlier studies, the growth volatility reducing influence of remittances flows was established. Second, unlike the extant literature, the growth volatility reduction potential of remittances was found to be more pronounced in the presence of well-functioning institutions. Finally, the interaction of remittances with our six institutional quality measures showed that growth volatility reduced considerably with better institutions. Practical implications – In terms of policy, remittances recipient countries need to simultaneously pursue economic and governance reforms. Both of these will enhance the counter-cyclicality of remittances and possibly other capital flows. Originality/value – Substantial efforts have been devoted to investigating the impact of remittances on output growth volatility, while very little research attention has been devoted to analysing the impact of institutions on the remittances– output growth volatility nexus.